Effect of compensatory mechanisms on postural disturbances and musculoskeletal pain in elite sitting volleyball players: Preparation of a compensatory intervention - Gawel, E.; Zwierzchowska, A. (International Journal of Environmental Research and Public Health, 2021)
The aim of the study was to identify the effect of compensatory mechanisms on the prevalence of sagittal spinal curvature deformity and musculoskeletal pain and to assess the interrelationships between those components in sitting volleyball players. Twenty-one elite Polish sitting volleyball players (age = 34.1 ± 7.5, BM = 77.9 ± 16.0) participated in the study in which direct participatory systematic observation and a non-invasive method were used. Both objective (anthropometric, spinal curvature-Idiag M360) and subjective (musculoskeletal ailments-NMQ = 7) measurements were performed. The Statistica 13.3 software package was used for statistical analyses. The neck, lower back (43%), and upper back (38%) were the most frequently reported painful areas. Of all participants, 76% reported sagittal spinal deformities. In the habitual position, the results indicated moderate correlations (r = 0.5, p < 0.05) between the lumbar concavity of the back and low back pain (LBP) and between thoracic convexity and LBP (r = 0.4, p < 0.05). Internal and external compensation have an effect on the prevalence of spinal curvature deformities in the sagittal plane, with thoracic hyperkyphosis (38%) and lumbar hyperlordosis (33%) being the most common. More severe lower and upper back pain were correlated with greater angles of thoracic kyphosis and lumbar lordosis in the habitual position.